Effect of Tension on Human Periodontal Ligament Cells: Systematic Review and Network Analysis - Sun, Changyun; Janjic Rankovic, Mila; Folwaczny, Matthias; Otto, Sven; Wichelhaus, Andrea; Baumert, Uwe (Frontiers in Bioengineering and Biotechnology, 2021)
Orthodontic tooth movement is based on the remodeling of tooth-surrounding tissues in response to mechanical stimuli. During this process, human periodontal ligament fibroblasts (hPDLFs) play a central role in mechanosensing and mechanotransduction. Various in vitro models have been introduced to investigate the effect of tension on hPDLFs. They provide a valuable body of knowledge on how tension influences relevant genes, proteins, and metabolites. However, no systematic review summarizing these findings has been conducted so far. Aim of this systematic review was to identify all related in vitro studies reporting tension application on PDLFs and summarize their findings regarding force parameters, including magnitude, frequency and duration. Genes, proteins, and metabolites expression data was extracted and summarized. Studies’ risk of bias was assessed using tailored risk of bias tools. Signaling pathways were identified by protein-protein interaction (PPI) networks using STRING and GeneAnalytics. According to our results, Flexcell Strain Unit® and other silicone-plate or elastic membrane-based apparatuses were mainly adopted. Frequencies of 0.1Hz and 0.5Hz were predominantly applied for dynamic equibiaxial and uniaxial tension, respectively. Magnitudes of 10% and 12% were mostly employed for dynamic tension while 2.5% for static tension. The 10 most commonly investigated genes, proteins and metabolites were identified, mainly involved in osteogenesis, osteoclastogenesis or inflammation. Gene-set enrichment analysis and PPI networks gave deeper insight into the involved signaling pathways. This review represents a brief summary of the massive body of knowledge in this field, and will also provide suggestions for future researches on this topic.